Partnership Dynamics of LGB People and Heterosexuals: Patterns of First Partnership Formation and First Cohabitation - Jeanette Bohr; Andrea Lengerer (European Journal of Population, 2024)
Abstract In this study we examine partnership dynamics among people with different sexual orientations in Germany. More specifically, we explore the process of first partnership formation and first cohabitation among men and women who self-identify as heterosexual, homosexual or bisexual. Given the various discriminations against same-sex lifestyles, and the limited opportunities to meet potential partners, we assume that lesbian, gay and bisexual (LGB) people form partnerships later in life and less frequently than heterosexuals. We further expect that the constantly improving social and legal climate for sexual minorities will lead to a reduction in differences in partnership behaviour by sexual orientation. We use retrospectively reported partnership biographies from the German Socio-Economic Panel, which was supplemented in 2019 with a boost sample of sexual and gender minority households. Using discrete-time event history models, we analyse nearly 15,000 episodes of being single and nearly 20,000 episodes of living without a partner in the household. Around 4.5% of these episodes are from people who self-identify as LGB. The results clearly show that patterns of partnership and coresidential union formation differ by sexual orientation. People with a homosexual orientation—and to a lesser extent people with a bisexual orientation—are less likely to enter into a first partnership and a first cohabitation than people with a heterosexual orientation. Significant changes occur across cohorts: LGB people from younger birth cohorts enter (cohabiting) partnerships much earlier and more frequently than those from older cohorts. Thus, the union formation patterns of LGB and straight people have converged slightly.
Keywords: 330; Life course; Partnership formation; Cohabitation; Sexual orientation; LGB people; Heterosexuals